Customized bariatric stents for sleeve gastrectomy leak: are they superior to conventional esophageal stents? A systematic review and proportion meta-analysis - Hamid, Hytham K. S.; Emile, Sameh H.; Saber, Alan A.; Dincer, Mursit; de Moura, Diogo T. H.; Gilissen, Lennard P. L.; Pescarus, Radu (Springer, 2021)
Objective Recently, there has been a burgeoning interest in the utilization of customized bariatric stents (CBS) for management of sleeve gastrectomy leak (SGL). We aimed to conduct a proportion meta-analysis to evaluate the cumulative efficacy and safety of these new stents and to compare them with the conventional esophageal stents (CES). Methods A systematic literature search of the PubMed, Cochrane Library, Scopus, Web of Science and Google Scholar databases was conducted through May 1, 2020. Primary outcomes were technical and clinical success and post-procedure adverse events of CBS and CES. Secondary outcomes were number of stents and endoscopic sessions per patient, and time to leak closure. A proportion meta-analysis was performed on outcomes using a random-effects model, and the weighted pooled rates (WPRs) or mean difference with 95% confidence interval (CI) were calculated. Results The WPR with 95% CI of technical success, clinical success, and stent migration for CBS were 99% (93-100%) I-2 = 34%, 82% (69-93%) I-2 = 58%, and 32% (17-49%), I-2 = 69%, respectively. For CES, the WPR (95% CI) for technical success, clinical success, and stent migration were 100% (97-100%) I-2 = 19%, 93% (85-98%) I-2 = 30%, and 15% (7-25%), I-2 = 41%, respectively. Adverse events other than migration were very low with both types of stents. On proportionate difference, CBS had lower clinical success (11%) and higher migration rate (17%) in comparison to CES. In successfully treated patients, CBS was associated with lower mean number of stents and endoscopic sessions, and shorter time to leak closure compared to CES. The overall quality of evidence was very low. Conclusions In treatment of SGL, there is very low level evidence that CES are superior to CBS in terms of clinical success and migration rate, though may require more stent insertions and endoscopic procedures. The evidence however remains very uncertain. Perhaps relevant to some types of stents, CBS are promising; however design modification is strongly recommended to improve outcomes.
Keywords: Bariatric stents; Endoscopic; Leak; Obesity; Sleeve gastrectomy